2000
DOI: 10.1159/000028344
|View full text |Cite
|
Sign up to set email alerts
|

Effect of TEI-6720, a Xanthine Oxidase Inhibitor, on the Nucleoside Transport in the Lung Cancer Cell Line A549

Abstract: To examine the effect of 2-(3-cyano-4-isobutoxyphenyl)-4-methyl-5-thiazolecarboxylic acid (TEI-6720), an inhibitor of xanthine oxidase, on purine metabolism in the lung cancer cell line A549, the activities of adenosine deaminase, purine nucleoside phosphorylase, adenine phosphoribosyltransferase, hypoxanthine guanine phosphoribosyltransferase, xanthine oxidase, and guanase together with pyrimidine nucleoside phosphorylase were measured with or without the addition of TEI-6720, and the extracellular concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 14 publications
0
10
0
3
Order By: Relevance
“…In the present study, febuxostat at concentrations up to 100 AM did not show significant effect on the purine or pyrimidine metabolic enzymes tested. A report by Yamamoto and colleagues using A549 cells, a human type II alveolar epithelial cell line, revealed that febuxostat had no effect on guanine deaminase, HGPRT or PNP at concentrations up to 16 AM (Yamamoto et al, 2000). Yamamoto et al also reported that febuxostat exerted no effect on the purine metabolic enzymes, adenine deaminase and adenine phosphoribosyl transferase, or on pyrimidine nucleoside phosphorylase, at concentrations up to 16 AM (Yamamoto et al, 2000).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the present study, febuxostat at concentrations up to 100 AM did not show significant effect on the purine or pyrimidine metabolic enzymes tested. A report by Yamamoto and colleagues using A549 cells, a human type II alveolar epithelial cell line, revealed that febuxostat had no effect on guanine deaminase, HGPRT or PNP at concentrations up to 16 AM (Yamamoto et al, 2000). Yamamoto et al also reported that febuxostat exerted no effect on the purine metabolic enzymes, adenine deaminase and adenine phosphoribosyl transferase, or on pyrimidine nucleoside phosphorylase, at concentrations up to 16 AM (Yamamoto et al, 2000).…”
Section: Discussionmentioning
confidence: 98%
“…A report by Yamamoto and colleagues using A549 cells, a human type II alveolar epithelial cell line, revealed that febuxostat had no effect on guanine deaminase, HGPRT or PNP at concentrations up to 16 AM (Yamamoto et al, 2000). Yamamoto et al also reported that febuxostat exerted no effect on the purine metabolic enzymes, adenine deaminase and adenine phosphoribosyl transferase, or on pyrimidine nucleoside phosphorylase, at concentrations up to 16 AM (Yamamoto et al, 2000). This current report and previously published data strongly supports the selectivity of febuxostat in the inhibition of XO activity.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike allopurinol (and its active metabolite oxypurinol), febuxostat is not a purine analog and inhibits only xanthine oxidase/dehydrogenase, not other enzymes in the purine and pyrimidine metabolic pathways [Edwards, 2009;Khosravan et al 2006b;Okamoto et al 2003]. In vitro studies have demonstrated how febuxostat potently and selectively inhibits human xanthine oxidase activity, whereas the activity of other enzymes, such as purine nucleoside phosphorylase, adenosine deaminase, and pyrimidine nucleoside phosphorylase, are affected by less than 4% [Yamamoto et al 2000].…”
Section: Managementmentioning
confidence: 99%
“…24 Febuxostat requires no conversion to an active form and, since it is structurally unrelated to purine or pyrimidines, is more selective for xanthine oxidase; it therefore does not interfere with other enzymes in the purine metabolism pathway. 25,26 Febuxostat inhibits both the reduced and oxidized forms of xanthine oxidase by binding with high affinity in a narrow channel leading to the molybdenum center of the enzyme and essentially obstructing substrate binding. 24 This enhanced mechanism produces more sustained reductions in sUA levels compared to allopurinol.…”
Section: Pharmacologymentioning
confidence: 99%